Global Transition in Higher Education: From the Traditional Model of Learning to a New Socially Mediated Model - Mbatha, Blessing (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This article reports on the pedagogical value of Web 2.0 tools at Unisa (i.e., whether these tools can improve teaching and learning). A quantitative approach was used to conduct the study, with a questionnaire as a data collection instrument. The sample size was 301 lecturers drawn using stratified sampling, with proportional allocation drawn from all Unisa colleges. Descriptive statistics were employed to analyse and interpret the data. The results show that Web 2.0 tools are playing a pivotal role when it comes to opening avenues and collapsing the transactional distance in an ODL institution. A combination of web technology and the trend of constructivism can transform the learning process. This article therefore recommends that Unisa sensitise its lecturers to the adoption of Web 2.0 tools as an innovative way to improve teaching and learning.